Sacra Scripta. Journal of the Centre for Biblical Studies. - Sînziana Pop, Andreea (Caietele Echinox, 2012)
The article reviews the book "Sacra Scripta: Journal of the Centre for Biblical Studies," Year VIII, nr. 1, edited by Stelian Tofana.